Gambaran Karakteristik, Pengetahuan dan Dukungan Keluarga pada Ibu Hamil dengan Anemia - Crismonica Alifia Putri (HEALTH CARE: JURNAL KESEHATAN, 2023)
Abstract Anemia in pregnancy is condition that the level of hemoglobin is under 11 g/dL in first and third trimester and under 10,5 g/dL in second trimester. Anemia in pregnancy can cause abortion, low birth weight and death. This study aims to find out the descriptive of characteristic, knowledge and family support in pregnant women. This research is simple descriptive research using purposive sampling. The 94 samples were recruited with purposive sampling. The measuring instrument used questionnare that have been tested for validity and reability and distributed online used google form. The analysis used the descriptive analysis to know the frequency distribution of characteristic, knowledge and family support. Majority of age were 20-35 years as many as 87,2%, majority of maternal age were third trimester as many as 59,6%, majority of pregnancy were primigravida as many as 51,1%, majority of educational were university as many as 53,2%, majority of working status were not working as many as 63,8%, majority of economic status were low as many as 43,6%, majority of knowledge were moderate as many as 53,2% and majority of family support were good as many as 51%. Pregnant women with anemia in this research had characteristics 20-35 years, third trimester pregnancy, primigravida pregnancy, university education, not working status, low economic status, had moderate knowledge and good family support. It’s suggested for nurse to give health education about anemia more frequent to increase women pregnancy knowledge about anemia and the family can give good support to pregnant women. Keywords: Anemia, Knowledge, Family Support, Preganncy